The Physical Basis for pH Sensitivity in Biomolecular Structure and Function, With Application to the Spike Protein of SARS-CoV-2 - Warwicker, Jim (Frontiers in Molecular Biosciences, 2022)
Since pH-sensitivity has fundamental roles in biology, much effort has been committed to establishing physical models to rationalise and predict pH-dependence from molecular structure. Two of the key challenges are to accurately calculate ionisable group solvation and hydration, and then to apply this modelling to all conformations relevant to the process in question. Explicit solvent methods coupled to molecular dynamics simulation are increasingly complementing lower resolution implicit solvent techniques, but equally the scale of biological data acquisition leaves a role for high-throughput modelling. Additionally, determination of ranges of structures for a system allows sampling of key stages in solvation. In a review of the area, it is emphasised that pH-sensors in biology beyond the most obvious candidate (histidine sidechain, with an unshifted pKa near to neutral pH) should be considered, that modelling can benefit from other concepts in bioinformatics, in particular modulation of interactions and function in families of homologues, and that it can also be beneficial to incorporate as many experimental structures as possible, to mitigate against small variations in conformation and to analyse larger, functional, conformational changes. These aspects are then demonstrated with new work on the spike protein of SARS-CoV-2, looking at the pH-dependence of variants, including prediction of a change in the balance of locked, closed, and open forms, at neutral pH, for the Omicron variant spike protein.